Analisis Indeks Resonansi dan Kerentanan Jembatan Rel Kereta Api Maros-Barru Berdasarkan Data Mikrotremor (Studi Kasus Jembatan WTT Maccini Baji) - Syahruni, Risda; Sulistiawaty, Sulistiawaty; Palloan, Pariabti; Kaharuddin, Kaharuddin (Progressive Physics Journal, 2024)
This research is a quantitative descriptive research that aims to analyze the value of natural frequency and amplification factor, as well as knowing the level of resonance and vulnerability of WTT Maccini Baji Railway Bridge. This research was conducted on the Maros-Barru Railway Line, especially the WTT Maccini Baji Railway Bridge, Lau District, Maros Regency, South Sulawesi Province. Data collection was carried out at 8 points (4 points on the bridge and 4 points on the ground around the bridge) with two measurement times at each point, day and night. Processing of microtremor data using Geopsy software with the HVSR (Horizontal to Vertical Spectral Ratio) method to obtain HVSR curves that produce natural frequency and amplification values. The results showed natural frequency values ranging from 2,36 – 6,64 Hz and amplification values ranging from 2,67 – 15,92. The resonance index value of the Maccini Baji WTT Bridge obtained ranges from 30,68% – 181,49% and is included in the low resonance classification which indicates the bridge has a solid structure and is safe from potential damage due to resonance. While the seismic vulnerability index is obtained with a value of 2,07 – 77,35 which shows that the high seismic vulnerability classification is more dominant at the point located on the ground.